Polymer-Coated Metal Organic Framework for Drug Delivery - Aljassim, Tasneem Jassim (2024)
A Master of Science thesis in Chemical Engineering by Tasneem Jassim Aljassim entitled, “Polymer-Coated Metal Organic Framework for Drug Delivery”, submitted in May 2024. Thesis advisor is Dr. Rana Sabouni. Soft copy is available (Thesis, Completion Certificate, Approval Signatures, and AUS Archives Consent Form).